Trypanocidal activity of genotoxic concentration of benznidazole on epimastigote forms of Trypanosoma cruzi - Edilson Nobuyoshi Kaneshima (Acta Scientiarum. Health Sciences, 2012)
The genotoxicity of benznidazole at a concentration of 75 μM, used in the treatment of Chagas' disease, has been recently reported. The present study evaluated the inhibitory effect of benznidazole on the growth of epimastigote forms of T. cruzi I and II by using genotoxic (75 μM) and non- genotoxic (50 μM) concentrations. To assess the growth rates of T. cruzi strains G2, A2.1A, CL, Y, and 2052, parasites in the epimastigote form were cultured in LIT medium for 192 h at 28oC, with (50 and 75 μM) and without (negative control) benznidazole. Benznidazole at both concentrations inhibited all the strains, regardless of genetic group. In the 75 μM concentration, there was a significant decrease in the number of parasites inoculated at T0 after 96 h incubation. The results showed that although genotoxic and non-genotoxic doses of benznidazole inhibit the growth of the epimastigote forms of T. cruzi I and II, only the 75 μM dose seem to indicate a possible trypanocidal effect.